ANALISIS PENGETAHUAN LINGKUNGAN TERHADAP PERILAKU PRO-LINGKUNGAN PADA MASYARAKAT KAMPUNG IKLIM KELURAHAN SUNGAI MIAI KOTA BANJARMASIN - Khairunnisa, Nur Asmi; Lilimantik, Emmy; Agusliani, Erma; Abidin, Zainal (EnviroScienteae, 2024)
Protecting the environment cannot be done by just one or two people or agencies but by all sides. It is the responsibility of us all to improve and change the condition of our environment. Thus, it is necessary to instill the attitude and character of caring and loving the environment from early on, especially in the young generation. The purpose of this study is to determine knowledge, attitudes, and environmental actions on pro-environmental behavior in the community of Sungai Miai Climate Village, as well as analyze the influence among knowledge, attitudes, and environmental actions on pro-environmental behavior of the Community of Climate Village Sungai Miai, Banjarmasin City. The sample of this research is a census taking all the people of the climate village who participate in the activities. Data collection with Likert scale questionnaire method and data analysis using SEM test through Lisrel 88 program. The results of the research data showed that environmental knowledge affects pro-environmental behavior, which is known as the effect of environmental knowledge with a t-value of 2.10 and an estimated coefficient of 0.31. That value is significant because the t-value> 1.96 is supported by the field facts that the community of Sungai Miai climate village often conducts counseling, training and socialization about the environment at their integrated service post. While the attitude has a t-value of -0.09 and an estimated coefficient of -3.30. The action value is 0.09 and the estimated coefficient is 3.23. This value is deemed insignificant because the t-value is not > 1.96 and the estimated value does not qualify as sufficiently high, there is no correlation between latent variables with latent variables of pro-environmental behavior. However, attitudes and actions have no impact on pro-environmental behavior due to a lack of public awareness of the environment and the lack of environmental facilities in their area.